Edible biopolymers with functional additives coatings for postharvest quality preservation in horticultural crops: a review - Krishnan, Rohan Rama; Olasupo, Abdulhakeem Dapo; Patel, Keya Himanshu; Bolarinwa, Islamiyat Folashade; Oke, Moruf Olanrewaju; Okafor, Catherine; Nkwonta, Chikere; Ifie, Idolo (Frontiers in Sustainable Food Systems, 2025)
Global concerns over the depletion of fossil fuels and their impact on the environment have resulted in the development of bio-based materials with more sustainable approaches. The need for a more sustainable economy and a reduction of fossil fuel dependency is driving research in this field. Biopolymers are chain-like molecular structures made of covalently attached monomeric units derived from renewable resources, microorganisms, or synthetic and biodegradable sources. Although biopolymer-based coatings have promising applications in postharvest preservation, they are often limited by their inherent properties when applied alone to fresh produce. This review focuses on assessing the efficacy and potential of biopolymer-based edible coatings in postharvest preservation, with a specific emphasis on the role of functional additives in enhancing performance. Furthermore, it explores how natural additives like essential oils, antioxidants, and antimicrobials interact with biopolymer matrixes in synergy, evaluating their enhanced functional properties in extending the shelf life of produce as well as their environmental impact and biodegradability. By analyzing interactions, release mechanisms, and comparative effectiveness of additives, the role and future of active ingredients in creating multifunctional preservation systems that meet food safety and sustainability requirements is presented.